PENINGKATAN LITERASI HALAL JAMA’AH PENGAJIAN MAJELIS TA’LIM NURUL IMAN GEJIKAN, GAGAK SIPAT, NGEMPLAK, KAB. BOYOLALI - Moch. Rusli; Muh. Nashirudin; Zulfikar Ali Ahmad; Asiah Wati (LPPM Universitas Abdurrab, 2024)
The Nurul Iman Ta'lim Majlis congregation is a community that has positive activities in its daily life and also consists of various types of professions within it. Routine activities, including the promotion of halal literacy, are carried out every Friday night. The importance of socializing halal literacy is because several business actors on the MSME scale need to carry out self-declaration of halal certification, which the government has provided. Lack of literacy causes a lack of public access and knowledge, so direct outreach is needed from experts, namely the Center for Halal Studies (PSH). The method used was training and outreach related to halal literacy and obtaining halal certification, which was carried out in Gejikan village, Gagaksipat, Boyolali, on June 22 2023. The results of the service carried out by the Sharia Faculty team at UIN Raden Mas Said Surakarta were attended by 50 congregations who participated in the outreach and were enthusiastic about the material as evidenced by several questions. There are 5 out of 50 congregations own MSME products and join in the halal certification process through a self-declaration process accompanied by PSH. Knowledge and socialization are delivered well, increasing scientific abilities and practices related to halal.